IMPLEMENTING ARTIFICIAL INTELLIGENCE BY SMALL ACCOUNTING FIRMS IN THE CONTEXT OF INDUSTRY 4.0: NECESSITY OR AN EXPENSIVE - Cristian Dragoș Țurcan; Andreea Gabriela Tănase; Andreea Măldăreanu; Raluca-Florentina Crețu; Viorel - Costin Banța (Annals of the University of Craiova: Economic Sciences Series)
Large accounting firms have invested huge sums in adopting artificial intelligence to increase internal efficiency and to improve customer engagement. Achieving the potential of artificial intelligence requires, in addition to short-term expenses, long-term expenses for the efficient use of AI systems. Also, developing customized artificial intelligence solutions comes with a high price, requiring specialists qualified in operating sophisticated software and significant research and development expenditures. This case study will analyze the barriers to the adoption of artificial intelligence and the impact that AI has on small accounting firms, in order to identify optimal solutions for transitioning to the new technology.